Military Arrangements for the Battle of Kadesh in 1274 BC During the Era of the New Kingdom (Journal of the College of Education for Women, 2022)
The Battle of Kadesh is replete with many military arrangements that reflect the tremendous development of war preparations in the thirteenth century BC; where the expressive pictures the Egyptians left on some of the walls of their temples show the tremendous ability to organize and divide the forces and the great development that affected the war machine. Furthermore, the text accompanied these pictures reveal some news about that battle, which is considered one of the most important wars in the ancient world. Thus, the importance of the study lies in the fact that it examines one of the most important battles of the ancient Near East, the results of which had great repercussions on the region. This is because it is the most abundant Bronze Age battle with regard to the sources from the Egyptian side, in contrast to the scarcity of the Hittite sources related to the battle. Accordingly, the research problem lies in the scarcity and oldness of the recital sources related to the events of the Battle of Kadesh where the available ones date back to periods following the battle. Besides, a large of number of these sources are Egyptian; in addition to the absence of impartial sources. Thus, it is very difficult to verify the arrangements made by the two sides and to ensure that victory claimed by both sides. The research aims thus to shed light on the military arrangements for that conflict that took place between the Egyptians and the Hittites at Kadesh, which ended with a peace treaty in 1270 BC to overcome the lack of Hittite sources. It also highlights the victory claims. Such a research helps to add a new reading on the reality of the conflict area after the war in order to come up with real and realistic results of the battle. Accordingly, the researcher relied on a historical, descriptive and analytical approach when recalling the events of the battle and describing the scenes to obtain the desired result. The research has come out with several conclusions related to the development of military thought with respect to managing wars and restoring the balance of power in the ancient Near East.